Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1038/s41598-017-13497-8
|View full text |Cite
|
Sign up to set email alerts
|

Surface marker profiling of SH-SY5Y cells enables small molecule screens identifying BMP4 as a modulator of neuroblastoma differentiation

Abstract: Neuroblastoma is the most common extra-cranial solid tumor in children. Its broad spectrum of clinical outcomes reflects the underlying inherent cellular heterogeneity. As current treatments often do not lead to tumor eradication, there is a need to better define therapy-resistant neuroblastoma and to identify new modulatory molecules. To this end, we performed the first comprehensive flow cytometric characterization of surface molecule expression in neuroblastoma cell lines. Exploiting an established clusteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 78 publications
(85 reference statements)
2
31
1
Order By: Relevance
“…To further evaluate the growth and differentiation variance of these cell lines at the protein level, we examined whether induction of two recently characterised inducers of differentiation, BMP4 [29] and EPAS1 [28], corresponded with the propensity of cells to differentiate. As shown in Figure 4A…”
Section: Immunoblotting and Immunohistochemistrymentioning
confidence: 99%
“…To further evaluate the growth and differentiation variance of these cell lines at the protein level, we examined whether induction of two recently characterised inducers of differentiation, BMP4 [29] and EPAS1 [28], corresponded with the propensity of cells to differentiate. As shown in Figure 4A…”
Section: Immunoblotting and Immunohistochemistrymentioning
confidence: 99%
“…Similarly, BMP2 was shown to induce growth arrest and neuronal differentiation of SH-SY5Y and RTBM cell-lines subsequent to accumulation of p27 (23). Although BMP2 has been shown to be a Wnt target gene in other cell types, our RNA-seq of Wnt3a/Rspo2 treated neuroblastoma cells highlighted BMP4 as the most prominent BMP gene downstream of Wnt/β-catenin signalling, and a recent study showed that BMP4 can trigger neurite-like extensions in SH-SY5Y cells, induce TrkA, and decrease MYCN and Ki-67 (24). Our study in part agrees with these findings, but with important differences and clearer mechanistic insights.…”
Section: Discussionmentioning
confidence: 61%
“…One of our most highly Wnt-induced genes following Wnt induction was BMP4. Previous studies have alluded to a role for BMPs in neuroblastoma growth and differentiation, including BMP2 in mouse neuroblastoma and SH-SY5Y cells (22,23) and BMP4, which also affected SH-SY5Y differentiation and decreased proliferation markers (24). However, the mechanisms and signalling crosstalk involved in BMP-mediated phenotypes and the significance to primary disease of BMPs is not known.…”
Section: Our Previous Work Demonstrated High-levels Of the Leucine Rimentioning
confidence: 99%
“…Human neural cells obtained from proliferation and differentiation conditions were screened for the expression of cell surface molecules using human BD Lyoplate screening panels as recently reported for neuroblastoma cells . For flow cytometric analysis, single cell suspensions were dispensed into 96‐well plates at 200,000–500,000 cells per well.…”
Section: Methodsmentioning
confidence: 99%